2017
DOI: 10.1007/s12639-017-0902-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Hepatozoon felis in Rhipicephalus sanguineus ticks infested on captive lions (Panthera leo)

Abstract: spp. are protozoan parasites that infect a wide range of domestic and wild animals. The infection occurs by ingestion of an infected tick. This study was carried out to detect and characterize spp. in ticks collected from captive lions () in Thailand based on the partial 18S rRNA gene sequence. A total of 30 ticks were collected and identified as . The collected ticks were separated into 10 tick pools by sex and life stages. Of the 10 tick pools examined, only one (10%) was found to be infected with the specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…So far, epidemiological data on H. silvestris were limited to European wild cats from Bosnia and Herzegovina [ 13 , 20 ] and a report of a positive feline blood sample from southern Italy [ 14 ]. Hepatozoon felis was considered the most common species infecting wild and domestic felids worldwide [ 6 , 14 , 16 , 26 28 ]. In Europe, infections of cats with H. felis mainly occur in Mediterranean countries where hematophagous arthropods are more abundant [ 8 , 12 , 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, epidemiological data on H. silvestris were limited to European wild cats from Bosnia and Herzegovina [ 13 , 20 ] and a report of a positive feline blood sample from southern Italy [ 14 ]. Hepatozoon felis was considered the most common species infecting wild and domestic felids worldwide [ 6 , 14 , 16 , 26 28 ]. In Europe, infections of cats with H. felis mainly occur in Mediterranean countries where hematophagous arthropods are more abundant [ 8 , 12 , 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies based on PCR-based assays as the reference diagnostic test for epidemiological studies, which given their greater sensitivity, particularly for testing different hosts with intermittent levels of parasitemia via a low infection rate by gamonts, as Otranto et al [ 114 ], Haklová-Kočíková et al [ 18 ], Jòzsef et al [ 24 ], Ramos et al [ 116 ], and Mitkova et al [ 120 ]. Notably, all the molecular evidence comes from the complete and partial sequences of the small subunit (SSU) ribosomal DNA (rDNA) 18S gene is a sufficient phylogenetic marker to approximate ordinal level relationships and those within orders [ 68 , 98 , 119 , 142 , 143 , 144 , 145 ]. Previous molecular studies of Harris et al [ 22 ] and Barta et al [ 19 ] demonstrated that the haemogregarine species are clustered in sister clades with interspecies linked more with the host geographic distribution, rather than host species.…”
Section: Resultsmentioning
confidence: 99%
“…Other bacteria species found to be abundant in (40)(41). In the United States, it is vectored by the Amblyomma maculatum nymphs or adults (39).…”
Section: Discussionmentioning
confidence: 99%